Bronchoalveolar lavage improves diagnostic accuracy in patients with diffuse lung disease. Issue 1 (14th June 2011) - Capelozzi, Vera Luiza; Faludi, Eduardo Polizini; Balthazar, Alípio Barbosa; Fernezlian, Sandra de Morais; Filho, João Valente Barbas; Parra, Edwin Roger
Abstract Bronchoalveolar lavage (BAL) is an established diagnostic tool in diffuse parenchyma lung disease. The objective of the present study was designed to investigate whether immunophenotyping affects BAL results and improves diagnostic accuracy. BAL from 61 patients was included in the study. The patients were also submitted to transbronchial biopsy, with a final diagnosis of granulomatous disease [tuberculosis (TB), n = 20; sarcoidosis (SARC), n = 3; and hypersensitivity pneumonitis (HP), n = 4]; idiopathic interstitial pneumonias (IIPs) [idiopathic pulmonary fibrosis (IPF), n = 9; organizing pneumonia (OP), n = 17]; and lung cancer (LC), n = 8. Immunohistochemistry and histomorphometry were used to identify and quantify type 1 and type 2 alveolar epithelial cells, macrophages, CD3+T‐cells, CD4+T‐cells, CD8+T‐cells, and CD20+B‐cells in BAL. These markers were correlated with a database and pulmonary function tests. The cellular, inflammatory, and immune components of BAL varied among the diagnostic groups and were negatively correlated with age and smoking history. An increased quantity of lymphocyte surface markers CD3 (P < 0.05) and CD20 (P = 0.01) was seen in IIPs. Patients with a pattern of OP had a higher proportion of type 2 alveolar epithelial cells; patients with SARC had a higher density of CD20+B‐cells and CD4+T‐helper cells; and patients with HP had a higher proportion of CD8+T‐cytotoxic cells. A positive association was found between the density of type I alveolar epithelial cells and forced vital capacity. The immunophenotyping affects the cellular, inflammatory, or immune constituents of BAL and improved the diagnostic accuracy in diffuse parenchymal lung disease. Diagn. Cytopathol. 2013. © 2011 Wiley Periodicals, Inc.